Flow ability and Mechanical Properties of Shotcrete concrete incorporated with Waste Plastic Fibers (Iraqi Journal of Civil Engineering, 2021)
Polyethylene terephthalate (PET) fiber is a green-friendly fiber that is capable of enhancing the mechanical properties of wet-mixing shotcrete. The main purpose of this study is to see how varied volumes of waste plastic fibers (WPF) affect the flowability and mechanical properties of wet-mix shotcrete. For this aim, a variety of experimental tests based on WPF content were chosen. Fresh and mechanical tests included slump, T500, density, compressive strength, and splitting strength were applied. The results shown a improved in shotcrete performance as the WPF content increased. Among all fitting correlations, density and compressive strength revealed the strongest linear ship association. Due to greater interlocking between WPF and concrete matrix, WPF was a major use in enhancing splitting tensile strength. WPF had the most influence on splitting strength, with 23–31 percent, 7–23 percent, and 6–38 percent for 7, 14, and 28-day, respectively.